(untitled) (Global Journal of Human-Social Science, 2016)
The major concern addressed in this study is why the University of Zambia (UNZA), despite being the first national University with so much vast experience in excellence and service as its motto is and being the first institution to offer distance education (DE) in Zambia, has not commensurately grown to competitive and comparative massive enrollment numbers, increased number of programmes and courses and development and delivery of instructional materials in Open and Distance Learning (ODL). The need to introduce DE at UNZA, amongst many other compelling reasons could be attributed to the Lockwood Commission, whose report in 1963/64 recommended that degree programmes at the Institution should be available by distance study to suitably qualified candidates who might not be in position to attend the University education on full -time basis. This study is anchored on questions such as: (i) How does UNZA run distance education? (ii) How does UNZA develop instructional materials? (iii) How does UNZA deliver instructional materials to its distance students? (iv) What successes has UNZA scored in distance education mode of study? (v) Why is distance education at UNZA not expanding as expected?